DESIGN OF BELT CONVEYOR TO INCREASE THE EFFICIENCY OF FINISHING GOOD PRODUCT TRANSFER FROM WAREHOUSE 1 TO WAREHOUSE 2 IN PT XY - M. Khamdi Muzakky (TRANSMISI, 2019)
This research aims to find out how much capacity that could have produced a conveyor according to the rpm speed of the motor and conveyor dimensions as well as to  determine the selection of the components that are used as system power supplier. This research was carried out based on the calculation of the design of conveyor design guide book and catalogue containing components of belt conveyor. Results of the design  is to be used as a guide for designing a conveyor to transport box containing intravenous fluids in PT XY. After the design resulted in two conveyors with 22.5 m long dimension, 40 cm wide belt and 0.5 m / s speed with inclination angle of 300 and 250. The conveyor has a carrying capacity of 300 boxes / hour (4.3 ton / jam). For power supply systems used 1.5 kw AC motor, WPX 80 type gearbox reducer ratio 1:10 s / d 1:60, S 400/4 type belt, drive pulley ???? 500 mm, roller idler ???? 89 mm, take-up type screws, transition roller chain number 40, number of teeth Z1= 21 and Z2=50, sprocket ???? 90.5 mm and ???? 209.5 mm, SAE type 10 oil (43 cSt, 200 SUS at 37.80C).